Gênero e o impeachment de Dilma Roussef: uma análise de páginas de facebook feministas e de mulheres ativistas na Amazônia - CASTRO, Luciana Gouvêa Hage de (Universidade Federal do Pará, 2018)
The political process of the impeachment of then-President Dilma Rousseff, the first woman elected to the highest executive position in Brazil, is the contextual framework of the research presented here, which will analyze communications from four Facebook communities run by women from Imperatriz Feminists of Imperatriz - Women and Affinity Forum - Feminist Articulation of Imperatriz), Manaus (Feminism in Manaus) and Rio Branco (Feminist Chat Acre). The temporal analysis was delimited from the three main phases of the process of impeachment, they are: the acceptance of the denunciation by the then president of the Chamber of Deputies Eduardo Cunha; the vote on this case in that Chamber; and the final verdict given by the Senators. As a problem question is presented: How was Dilma Rousseff's impeachment in communicative constructions approached in the feminist / women activist profiles of Amazonian women? The hypothesis is based on the assumption that profile communications, although they have a political activism in the cause of women, did not discuss the gender issue in Dilma Rousseff's removal, there was in fact a silencing with regard to this issue. theme. As a methodology, we start with qualitative research, based on content analysis in the light of Laurence Bardan (2002). These scientific elements will provide the necessary basis for a better understanding of the problem issue and the proposed objectives, based on the discussions about the women's political movement, the feminist movement, citizenship, cyberfeminism and political activism. Thus, the authors who founded the investigation were: Simone de Beauvoir (1949); Judith Buther (2003); Maria Luzia Álvares (1995, 1997; Manuel Castells (2015); Flávia Biroli (2014), among others. This research intends to be a collaboration for a better understanding of the political participation of the Amazon woman in the scenario lived in the impeachment of the president Dilma Rousseff; and in general, the causes of women, who daily struggle for a more egalitarian space in society, especially in the Amazon.